Desarrollo de una aplicación web para la gestión de materia prima y control de ventas en la empresa Breldy del cantón Yantzaza. - Salinas Minga, Nayo Francisco (2023)
Currently, the development of information technology (IT) solutions in companies has increased exponentially in the most recent years, with the aim of reducing some costs and increasing up the profits. The digitalization of production processes helps companies redefine resources to face a crisis or improve their business practices. In this context, the Breldy company has dedicated to the production of craft beer, which was observed to lack the automation of its processes in the entry of raw materials, production of goods, and control of sales made, which is why the following response arose. research question: How would the development of a web application influence the management of raw materials and sales control in the Breldy company in the Yantzaza canton? For this, the Titration Work was developed under the XP methodology, the 4+1 architecture was implemented showing the logical and physical design of the application based on the system necessities validated by the company's client, which were documented with the IEEE 830 standard. Subsequently, these models were coded based on the Client-Server architecture, and the frontend and backend were developed with Vue, Node, Express and MySQL, obtaining as a software product an application that contributes to the management of processes. of the company. Finally, tests were carried out on the API-REST services in a simulated environment to guarantee the integration of future applications, load and stress tests to measure the performance of the application and finally functional tests where the client participated evaluating the application. In its whole. So, tt is concluded that the Breldy web application offers a solution to the problem upstretched, by providing the company with a centralized and automated platform for the management of critical processes. This is achieved through the use of forms, charts and Kardex cards, allowing strategic decisions to be made in a timely manner to benefit the company in the nearest future. Keywords: Software project management, Software development, XP Methodology, SMEs, Breldy company.